2004
DOI: 10.1111/j.1365-2672.2004.02236.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Bacillus subtilis spore resistance to and killing by aqueous ozone

Abstract: Aims: To determine the mechanisms of Bacillus subtilis spore killing by and resistance to aqueous ozone. Methods and Results: Killing of B. subtilis spores by aqueous ozone was not due to damage to the spore's DNA, as wild-type spores were not mutagenized by ozone and wild-type and recA spores exhibited very similar ozone sensitivity. Spores (termed a ) b ) ) lacking the two major DNA protective a ⁄ b-type small, acid-soluble spore proteins exhibited decreased ozone resistance but were also not mutagenized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 57 publications
(206 reference statements)
4
76
0
5
Order By: Relevance
“…About this form, an ozone treatment in organic wastes can be considered an effective and faster form, that other treatments with chlorine or hydrogen peroxide (Glaze;Kang and Chapin, 1987;King, 2001;Campos et al, 2006). In addition, the treatment with ozone is not exclusive and can be combined with the use of hydrogen peroxide or ultraviolet radiation, harnessing therefore the results by a synergic effect (King, 2001;Young and Setlow, 2004). Another property of ozone is the capacity of absorption of flavors and strange smells in the water.…”
Section: Properties Of Ozonementioning
confidence: 99%
See 2 more Smart Citations
“…About this form, an ozone treatment in organic wastes can be considered an effective and faster form, that other treatments with chlorine or hydrogen peroxide (Glaze;Kang and Chapin, 1987;King, 2001;Campos et al, 2006). In addition, the treatment with ozone is not exclusive and can be combined with the use of hydrogen peroxide or ultraviolet radiation, harnessing therefore the results by a synergic effect (King, 2001;Young and Setlow, 2004). Another property of ozone is the capacity of absorption of flavors and strange smells in the water.…”
Section: Properties Of Ozonementioning
confidence: 99%
“…At lowest pH, the mechanism of ionic reaction predominates (ozonolisys) and generates the peroxide production (Seafish, 1997;Guzel-Seydim et al, 2004;Bocci, 2006). Ozone technology has several significant advantages over its chemical alternatives i) Ozone can be generated on-site; ii) Ozone is one of the most active, readily available oxidizing agents; iii) Ozone rapidly decomposes to oxygen leaving no traces; iv) Reactions do not produce toxic halogenated compounds; v) Ozone acts more rapidly, and more completely than other common disinfecting agents do; vi) Ozone reacts swiftly and effectively on all strains of viruses (Brooks and Pierce, 1990;Ibanoglu, 2002;Tapp and Sopher, 2002;Young and Setlow, 2004;Chawla, Bell and Marlene, 2007). Ozone has a longer half-life in the gaseous state than in aqueous solution (Table 5).…”
Section: Properties Of Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that coat proteins are important in protecting spores against a number of chemicals, including sodium hypochlorite, chlorine dioxide, and ozone, and cotE or chemically decoated wild-type spores are much more sensitive to these agents than are intact wild-type spores (37,40,41). This was also seen in the current work when extremely dilute sodium hypochlorite was used, as cotE spores were more sensitive than wild-type spores, and gerE spores were even more sensitive (Fig.…”
Section: Vol 190 2008 Properties Of Severely Coat-deficient Spores mentioning
confidence: 99%
“…Researchers have found that it can damage cell membranes (Scott & Lesher, 1963;Murray et al, 1965;Kim et al, 1999;GuzelSeydim et al, 2004;Cho et al, 2010), facilitate protein denaturation and enzyme activity decrease (Hinze et al, 1987;Mehlman et al, 1987;Takamoto et al, 1992;Komanapalli & Lau, 1996), as well as destroy the nucleic acids of microbes (Scott & Lesher, 1963;Roy et al, 1981;Mura & Chung, 1990; Hunt & Mariñas, 1999). Other studies have investigated the effect of ozone on the spore inner membrane of Bacillus subtilis (Young & Setlow, 2004;Cortezzo et al, 2004), and on the spore morphologies of Bacillus atrophaeus as well as Geobacillus stearothermophilus (Mahfoudh et al, 2010). It was also showed that ozone inactivated Pseudomonas aeruginosa ATCC27853 by the combined results of increased cytoplasmic membrane permeability and cytoplasm coagulation, rather than by severe membrane disruption and cell lysis (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%